Role of ICT tool in Acquisition of Proficiency in English Language- A Case Study on Outcome of Using MePro Pearson Software Tool - et. al., P. Haripriya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Proficiency in English, both writing and communication are considered as the most important life skills of the modern era. These skills are considered as an asset for lifelong learning and aids in recruitment process or sustainability in the job. This may even endeavor to reduce psychological stress while speaking or reading within the group and among the group. These days learning through online has become the order of the day. This paper presents the real need and priorities to learn English language through ICT (Information through Communication Technology) tools. The researcher of English department has found the students’ opinion and experience on use of ICT tools for enhancing the skills in English language. This paper investigates how English language tool, MePro from Pearson has helped students for employability and career development. A survey on MePro is tested and experienced by GPREC (G.Pulla Reddy Engineering College) students in the transformation of the student to achievement level with first hand practical knowledge is taken as a case study in the paper.